Pemberdayaan Masyarakat melalui Bazar Murah dan Kelas Ceria dalam Bidang Pendidikan dan Sosial - Ondy (Assoeltan: Indonesian Journal of Community Research and Engagement, 2024)
Mentoring activities aim to increase public awareness about social issues and develop students' abilities in creating creative Public Relations campaigns, while forming children's character through the Ceria Class and strengthening solidarity between Communication Science students at UBSI. The Bina Sarana Informatika University (UBSI) "Education–Social and Nonprofit Campaign" campaign method involves holding two main activities, namely Cheerful Classes and Cheap Bazaar, with a mentoring approach such as Awareness Building, Capacity Building, and Character Building. The committee team, with divided roles, works together in planning, implementing and evaluating these activities to achieve campaign goals and strengthen solidarity between Communication Science students at UBSI. The result of this assistance is that from the beginning of preparation to the final evaluation, the campaign committee team "Community Empowerment through Cheap Bazaars and Cheerful Classes in Education and Social Sectors" has shown strong commitment and extraordinary hard work. A solid leadership structure, successful event execution, careful monitoring and thorough evaluation have been the foundation for the success of this campaign. Through solid teamwork, this campaign succeeded in empowering the community, building solidarity, and providing positive contributions for all parties involved. Thus, this campaign not only achieved its stated objectives, but also provided valuable learning for future activities.